The mediating effect of personal values on the relationships between attitudes, subjective norms, perceived behavioral control and intention to use - Dalila, .; Hamrila, Abdul Latip; Norizan, Jaafar; Ikhwan, Aziz; Asyraf, Afthanorhan (Growing Science, 2020)
In recent years, the issue of food packaging waste has become a vital environmental concern in the society which revolves around waste management practices particularly among food hawkers. The problem has been highlighted by many researchers and numerous suggestions have been made in order to improve sustainability with regard to green environment. Food packaging waste ranks the highest contributor to waste. Thus, environmentally friendly food packaging (EFFP) has been introduced in the market to ensure good management practices could be promoted among food hawkers so that environmental pollution can be reduced. However, even though many environmental programs have been implemented, the usage of EFFP among food hawkers has not improved. Hence, this paper aims to propose a specific actual behavior model to determine the usage of EFFP among food hawkers with personal value as a mediator. The development of the model used data that were collected from local food hawkers. Structural equation modeling was used to test related hypotheses. The findings indicated that personal values were a suitable mediator construct. Furthermore, attitudes, subjective norm, and perceived behavioral were all found to have had significant effects on the intention to use and the actual behavior. Finally, this paper also discusses the limitations of the present study and the contribution it has made.